2023
DOI: 10.1097/mco.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diets, exercise performance, and training adaptations

Abstract: Purpose of reviewThe ketogenic diet has been proposed as a nutritional strategy in sports. This review was undertaken to provide an overview of the recent literature concerning the effects of ketogenic diet on exercise performance and training adaptations. Recent findingsMost recent literature on the ketogenic diet and exercise performance showed no beneficial effects, especially for trained individuals. During a period of intensified training, performance was clearly impaired during the ketogenic intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In CrossTraining athletes, it has been observed that similar changes in 400 m sprint and VO 2peak occurred in both ketogenic and non-ketogenic protocols [ 10 ]. This might be partially explained by the metabolic flexibility reached after full adaptation to the nutritional ketosis [ 36 ] which is associated with the mitochondrial dynamics and anti-oxidative capacity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CrossTraining athletes, it has been observed that similar changes in 400 m sprint and VO 2peak occurred in both ketogenic and non-ketogenic protocols [ 10 ]. This might be partially explained by the metabolic flexibility reached after full adaptation to the nutritional ketosis [ 36 ] which is associated with the mitochondrial dynamics and anti-oxidative capacity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to note the considerable number of dropouts among participants, particularly in the initial weeks of the KD nutritional intervention. It seems that the first weeks of the KD negatively affect physical performance due to alterations in perceived exertion, directly influencing adherence to the training and nutrition program [ 36 ]. Additional research is needed to assess whether this adherence issue occurs when individuals are unfamiliar with carbohydrate restriction.…”
Section: Discussionmentioning
confidence: 99%